Heart Angiotensin-Converting Enzyme and Angiotensin-Converting Enzyme 2 Gene Expression Associated With Male Sex and Salt-Sensitive Hypertension in the Dahl Rat - Ytrehus, Kirsti; Ludvigsen, Stian; Mancusi, Costantino; Gerdts, Eva; de Simone, Giovanni (Frontiers in Physiology, 2021)
Angiotensin-converting enzyme 2 (ACE 2) in the heart including its sex dependency in the hypertensive heart, has not been much studied compared to ACE. In the present study, we used the Dahl salt-sensitive rat exposed to fructose and salt to model a hypertensive phenotype in males, females, and ovariectomized females. Blood pressure was measured by the tale-cuff technique in the conscious state. Expression of RAS-related genes ACE, ACE2, angiotensin II receptor type 1, Mas1, and CMA1 in the heart were quantified. The results revealed small but significant differences between male and female groups. The main results indicate the presence of a male preponderance for an increase in ACE and ACE2 gene expression. The results are in accordance with the role of androgens or male chromosomal complement in controlling the expression of the two ACE genes.